Potential for Forecasting UK Summer Grass Growth from the North Atlantic Oscillation - Kettlewell, P. S.; Easey, J.; Hollins, P. D.; Martyn, T.; Stephenson, D. B. (UKnowledge, 2023)
The North Atlantic Oscillation (NAO) is a large-scale atmospheric circulation pattern which is well-known to influence the UK winter climate (Wilby et al., 1997). Recently, it has been shown that the winter NAO also affects summer rainfall in the UK (Kettlewell et al., 2003). Since water supply is an important limitation to summer grass growth in many parts of the UK, the winter NAO may influence summer growth. The objective of this study was to test the hypothesis that there is a relationship between the winter NAO and summer grass growth using data from reference plots at North Wyke in Devon.